ENHANCED MWCNT HYBRID ECG ELECTRODES ON THE BIO-SIGNAL RESPONSES (CAHIERS MAGELLANES-NS, 2024)
The non-invasive instrumental diagnostic methods like ECG, use surface electrodes as an interface for wearability on patient body, similar to health monitoring systems. Traditionally, these electrodes are conductive metal like -Ag/AgCl based, hardly upgraded ever. Nonmetal- conductive carbon-based materials like CNT, GO, rGO, Graphene, Graphite etc. have been studied extensively for their versatility characteristics giving scope for changes. Present study used Graphite MWCNT hybrid ECG (GCHE) electrode fabricated by electrophoretic deposition (EPD) technique. In the course of fabrication, biocompatible surfactants were used as dispersant of highly hydrophobic MWCNT, to coat Graphite electrodes. The resulting GCH electrode is dry type and exhibit characters of wearable health systems.